Applications and Advances of Regenerative Medicine in Surgery: A Systematic Review (Prisma) - Joahnni Raúl Clark Rivera Padilla; Luis Fernández de Córdova Río de la Loza; Arnulfo Erick de la Paz Martínez (International Journal of Medical Science and Clinical Research Studies, 2026)
Background: Regenerative medicine aims to repair, regenerate, or replace human cells, tissues, and organs in order to restore normal function, offering innovative solutions to surgical challenges through cell therapy, biomaterials, bioprinting, and tissue engineering. Objective: To assess the applications and advances of regenerative medicine in surgery. Methods: A systematic review was conducted following the PRISMA guidelines. A literature search was performed in PubMed, ClinicalKey, ISI Web of Science, ScienceDirect, and Google Scholar for studies published between 2022 and 2026. Articles reporting clinical studies involving human surgical patients were included. After applying the inclusion and exclusion criteria, 26 articles were selected for analysis. Results: In cardiovascular surgery, decellularized homografts showed excellent 5-year outcomes, with a mortality rate of 2.5% and a reintervention rate of 6.5%, while mesenchymal stem cells (MSCs) modulated the post-infarction inflammatory response. In ophthalmology, cell transplantation restored the ocular surface and improved visual outcomes. In trauma and orthopedic surgery, MSC-based tissue engineering showed outcomes equivalent to autologous bone grafting for the treatment of nonunion. In vascular surgery, acellular tissue-engineered vessels (ATEVs) demonstrated high patency rates and absence of rejection. Platelet-rich plasma (PRP) enhanced the healing of chronic wounds. In plastic surgery, autologous skin substitutes demonstrated stability at 5 years. Discussion: Current evidence supports the safety of regenerative therapies; however, their efficacy varies according to the underlying condition and clinical context. Multimodal approaches combining cells, growth factors, and scaffolds appear to outperform monotherapies, particularly in chronic wound healing and bone regeneration. Conclusion: Regenerative medicine offers a broad and promising therapeutic armamentarium with favorable safety profiles. Personalized combinations of therapeutic modalities guided by individual patient characteristics may represent the pathway toward transforming these strategies into established treatments.